+0  
 
+1
86
2
avatar+173 

(a) Simplify \(\frac{\binom{n}{k}}{\binom{n}{k - 1}}\).

(b) In the expansion of \((1 + x)^n\), there exist three consecutive coefficients a, b, c that satisfy a:b:c = 1:7:35. Find the positive integer n.

 Feb 27, 2020
 #1
avatar+109499 
+2

a.

 

                    n!

                _______

                 (n - k)! k!

             ___________                          =

                     n!

          _________________

           [n - ( k - 1)]! (k - 1)!

 

 

 

                     [ (n - k) + 1 ] ! (k - 1)!                                            

                    ___________________  =                                 

                       (n - k)!  k!                                                              

 

 

                    [ (n - k) + 1 ] !          ( k - 1)!

                   ____________   *   _______  =

                       (n - k)!                      k!

 

 

                       ( n - k + 1)

                      __________       

                               k

 

 

cool cool cool

 Feb 27, 2020
 #2
avatar+109499 
+2

 

Let  k-1  be  the  first coefficient we are looking for in the nth row of Pascal's Triangle

The second coefficient will be the  kth element  on row n  

And the last coefficient  will be the (k + 1) st  element  on row  n

 

 

We  have seen  that    C(n , k)  / C( n,  k  -1)  =  (n - k + 1) / k    

 

So...we can calculate   C( n, k + 1) / C ( n ,k)  as

 

      n!                                         ( n - k)!  k!

________________  *             _________   =

[ n - (k+ 1)]! (k+ 1)!                          n!

 

 

( n - k)!                          k!

__________   *          ______  =

[ n - (k + 1)]!                (k + 1)!

 

 

( n - k)!                  1

________  *       _____  = 

 (n - k - 1)!            k + 1

 

    n - k

________

     k + 1

 

 

So   we have these two equations

 

(n - k + 1)  / k =   7

(n-k) / (k + 1)  =  5         simplify

 

 

n  - k + 1   =  7k

n - k  = 5 (k + 1)

 

 

n - k  + 1  = 7k

n - k  = 5k + 5

 

n - 8k =  -1

n - 6k  =   5      subtract these

 

-8k + 6k  =  - 6

 

-2k  = - 6

 

k =  3

 

And

 

n  - 8k  =  -1

 

n  -8(3)  =  -1

 

n - 24  = -1

 

n =  23

 

Check : 

 

The coefficients  should be

 

C (n, k -1), C( n , k) and  C( n, k + 1)  =

 

C (23 , 2)  , C (23, 3)  and  C (23, 4)  =

  

253  ,  1771   and  8855

 

The ratios  are

 

1  :  1771/253  :   8855/253   =

 

1  : 7  : 35

 

 

cool cool cool

 Feb 27, 2020

35 Online Users

avatar
avatar
avatar
avatar
avatar
avatar
avatar
avatar